Answer:
3
Step-by-step explanation:
The answer is
the second graph.![\frac{x}{3} \leq 2](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx%7D%7B3%7D%20%5Cleq%202)
You need to isolate x, in order to do this you need to multiply both sides by 3, or 3/1
2*3 = 6
x/3 * 3 = x
Your equation should now be
So the circle should be filled in and pointing towards the left starting from 6
Answer:
-16
Step-by-step explanation:
X-6= -22
X = -22+6
X = - 16
Answer:
Nope. Does not satisfy pythagoras theorem
Step-by-step explanation:
72 squared does nit equal 45 squared plus 56 squared
Answer:
y= -6x +1
Step-by-step explanation:
The equation of a line is usually written in the form of y=mx +c, where m is the gradient (or slope) and c is the y-intercept.
In order to find the equation of a line, you would need 2 things:
① Gradient (← can be found)
② Coordinate (✓ we have 2 coordinates here)
To find the gradient, use the gradient formula below:
![gradient = \frac{y1 - y2}{x1 - x2}](https://tex.z-dn.net/?f=gradient%20%3D%20%20%5Cfrac%7By1%20-%20y2%7D%7Bx1%20-%20x2%7D%20)
![m = \frac{ - 5 - ( - 17)}{1 - 3} \\ m = \frac{ - 5 + 17}{ - 2} \\ m = \frac{12}{ - 2} \\ m = - 6](https://tex.z-dn.net/?f=m%20%3D%20%20%5Cfrac%7B%20-%205%20-%20%28%20-%2017%29%7D%7B1%20-%203%7D%20%20%5C%5C%20m%20%3D%20%20%5Cfrac%7B%20-%205%20%2B%2017%7D%7B%20-%202%7D%20%20%5C%5C%20m%20%3D%20%20%5Cfrac%7B12%7D%7B%20-%202%7D%20%20%5C%5C%20m%20%3D%20%20-%206)
Substitute the value of m into the equation:
y= -6x +c
To find the value of c, substitute a pair of coordinates.
When x=1, y= -5,
-5= -6(1) +c
c -6= -5
c= 6 -5
c= 1
Thus, the equation of the line is y= -6x +1.